Brazing sheet for joint structure of heat exchanger, joint structure of brazing sheet for heat exchanger, and heat exchanger
By incorporating copper into the core material of brazing sheets for heat exchangers and keeping the brazing and sacrificial anode layers copper-free, the configuration enhances corrosion resistance by diffusing copper into the fillet, thus preventing preferential corrosion and maintaining effective sacrificial anodic action.
Patent Information
- Application Number
- JP2019188043
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-10-11
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2039-10-11
AI Technical Summary
Existing brazing sheets for heat exchangers face challenges in preventing preferential corrosion of fillets formed at acute angle bonding structures, which reduces corrosion resistance due to copper segregation and interference with sacrificial anode action.
A brazing sheet configuration where the core material contains copper within a specified range, and the brazing and sacrificial anode material layers are substantially copper-free, allowing copper to diffuse and concentrate in the fillet, thereby reducing excessive potential mitigation by zinc and enhancing sacrificial anodic action.
This configuration effectively suppresses preferential corrosion of the fillet and improves corrosion resistance at the joints of the heat exchanger by maintaining a good sacrificial anodic action.
Smart Images

Figure 0007660311000001 
Figure 0007660311000002 
Figure 0007660311000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a brazing sheet used in a member constituting a heat exchanger, a joining structure for joining the brazing sheets together, and a heat exchanger having the joining structure. [Background technology]
[0002] A typical heat exchanger usually has tubes and fins, with multiple fins attached to the outer circumference of the tubes. Copper (Cu) or its alloys (for convenience, referred to as "copper materials") have been used as the material for the tubes, but aluminum (Al) or its alloys (aluminum materials) have also been used in recent years. Aluminum materials are generally used as the material for the fins.
[0003] In manufacturing heat exchangers, brazing material is generally used to attach fins to tubes. If both the tubes and fins are made of aluminum, for example, a brazing sheet is used in which at least one surface of an aluminum alloy core is clad with a brazing material layer. Considering the corrosion resistance of the tubes and fins, a brazing sheet is used in which one surface of the core is clad with brazing material and the other surface is clad with a sacrificial anode material layer.
[0004] The brazing material is generally an aluminum-silicon (Si) alloy used for brazing aluminum alloys, and the sacrificial anode material is generally an aluminum alloy with zinc (Zn) added to make its potential more base. A typical sacrificial anode material is an aluminum-silicon alloy brazing material with zinc added. This allows the sacrificial anode material to function as a brazing material as well.
[0005] One example of a brazing sheet clad with a sacrificial anode material layer is disclosed in, for example, Patent Document 1. Patent Document 1 discloses an aluminum alloy brazing sheet used in automotive heat exchangers, particularly as a passage component for fluids (cooling water, refrigerants, etc.), in which the components of the core material and sacrificial anode material are adjusted to achieve good brazing properties and excellent strength and corrosion resistance after brazing.
[0006] In this brazing sheet, the content of silicon, iron (Fe) and manganese (Mn) in the sacrificial anode material is restricted to 0.15 mass% or less. This is to suppress the generation of Al-Mn-Si or Al-Fe-Mn-Si compounds and suppress the decrease in strength after brazing. In addition, in this brazing sheet, the content of silicon in the core material is also restricted to 0.15 mass% or less, and copper is added to the core material in the range of 0.40 to 1.2 weight%. The reason for adding copper is to improve the strength of the core material, make the potential of the core material more noble, increase the potential difference with the sacrificial anode layer, etc., and improve the corrosion prevention effect by the sacrificial anode action.
[0007] Another known example of a brazing sheet clad with a sacrificial anode material layer is disclosed in Patent Document 2. Patent Document 2 also discloses an aluminum alloy brazing sheet used in automotive heat exchangers, particularly as a fluid passage component, which has a sacrificial corrosion protection effect on both sides and a brazing function on one side, and further has adjusted components of not only the core material and sacrificial anode material but also the brazing material to prevent preferential corrosion of the joint.
[0008] In this brazing sheet, zinc (Zn) is added not only to the sacrificial anode material but also to the brazing material, and copper is further added to the brazing material in the range of 0.1 to 0.6 mass%, and copper is also added to the core material in the range of 0.05 to 1.2 mass%. The purpose of adding copper to each material is different: in the brazing material, it is to make the potential of the brazing material more noble, and in the core material, it is to improve the strength of the core material. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2010-163674 A [Patent Document 2] JP 2013-155404 A Summary of the Invention [Problem to be solved by the invention]
[0010] In the brazing sheet disclosed in Patent Document 1, the addition of copper to the core material improves the strength and improves the anticorrosive effect by the sacrificial anode action. However, in this brazing sheet, the silicon content of both the sacrificial anode material and the core material is limited to 0.15 mass% or less, and the content of various metal elements other than copper in the core material is also specified in detail. Therefore, the range of options for materials that can be used as the core material and the sacrificial anode material is narrowed. Moreover, in this brazing sheet, the silicon content of the sacrificial anode material is restricted to a very small amount. Therefore, it is considered that this sacrificial anode material layer does not function as a general brazing material.
[0011] In the brazing sheet disclosed in Patent Document 2, by adding copper together with zinc to the brazing material, not only zinc but also copper is concentrated at the brazing joint. Therefore, this copper concentration (containment) is intended to prevent the potential of the joint from becoming too noble due to zinc. However, as a result of intensive research by the present inventors, it has become clear that when copper and zinc are used in combination, the preferential corrosion action of the sacrificial anode material layer is reduced, resulting in a decrease in corrosion resistance.
[0012] For example, some types of heat exchangers include a structure in which the angle formed by the joining surfaces of the brazing sheets when they are joined together is an acute angle. For convenience, if such a structure is referred to as an "acute angle joining structure" and the surfaces of the brazing sheets that are adjacent to the joining surfaces and are not joined are referred to as "non-joining adjacent surfaces," in such an acute angle joining structure, a fillet is formed between the non-joining adjacent surfaces that form an acute angle with each other. In this specification, this fillet is defined as the solidification of the brazing material or sacrificial anode material that flows out from the joining surfaces during joining.
[0013] When copper and zinc are used in combination in the brazing material as in Patent Document 2, copper segregates on the surface of the fillet after brazing. Since the segregated copper functions as a cathode in the corrosion reaction, the corrosion priority action of the sacrificial anode layer present around the segregated copper is reduced, resulting in a decrease in corrosion resistance. In addition, the sacrificial anode layer present around the segregated copper on the fillet surface becomes noble. This reduces the potential difference between the sacrificial anode layer and the core material, which also reduces the function (preferential corrosion action) of the sacrificial anode layer. Depending on the situation, there is a risk of early penetration due to intergranular corrosion of the core material.
[0014] The present invention has been made to solve such problems, and has an object to effectively suppress or prevent preferential corrosion of a fillet formed adjacent to the joint between brazing sheets, even if the fillet contains copper and zinc, thereby improving the corrosion resistance of the heat exchanger. [Means for solving the problem]
[0015] In order to solve the above-mentioned problems, the brazing sheet according to the present invention is a brazing sheet used in a heat exchanger, comprising: an aluminum alloy core material; a brazing material layer coated on one surface of the core material and made of an aluminum alloy brazing material containing silicon (Si); and a sacrificial anode material layer coated on the other surface of the core material and made of a sacrificial anode material of an aluminum alloy containing zinc (Zn) in the range of 0.5 to 6.0 mass % and silicon (Si) in the range of 3.0 to 11 mass %, The brazing filler material and the sacrificial anode material have a joining surface which is joined together to form a joint, and a non-joining adjacent surface adjacent to the joining surface, the joining surface being the sacrificial anode material layer, and when the joining surfaces are joined together, a fillet is formed in a portion between the non-joining adjacent surfaces and adjacent to the joining surfaces, where the sacrificial anode material flows out from the joining surfaces and solidifies, and neither the brazing filler material nor the sacrificial anode material contains copper (Cu), and the core material contains copper (Cu) in the range of 0.3 to 1.2 mass %.
[0016] Alternatively, in order to solve the above-mentioned problems, the brazing sheet according to the present invention may be a brazing sheet used in a heat exchanger, comprising: an aluminum alloy core material; and a sacrificial anode material layer coated on both sides of the core material and made of an aluminum alloy sacrificial anode material containing zinc (Zn) in the range of 0.5 to 6.0 mass% and silicon (Si) in the range of 3.0 to 11 mass%, wherein the brazing sheet has joining surfaces which are joined together to form a joint, and non-joining adjacent surfaces which are adjacent to the joining surfaces, the joining surfaces being the sacrificial anode material layer, and when the joining surfaces are joined together, a fillet is formed in which the sacrificial anode material has flowed out from the joining surfaces and solidified, and the sacrificial anode material does not contain copper (Cu), and the core material contains copper (Cu) in the range of 0.3 to 1.2 mass%.
[0017] Furthermore, in order to solve the above-mentioned problems, the brazing sheet joint structure according to the present disclosure is used in components constituting a heat exchanger, and is a joint structure in which brazing sheets are joined together, each having an aluminum alloy core material coated with a sacrificial anode material layer made of a sacrificial anode material on at least one surface thereof, the brazing sheets having a joint surface and a non-joining adjacent surface adjacent to the joint surface, each of the joint surfaces being the sacrificial anode material layer, and a fillet formed of the sacrificial anode material that has flowed out from the joint surface and solidified between the non-joining adjacent surfaces, the fillet containing 2.0 mass % or less copper (Cu), which is a concentration that exceeds that of the core material and the sacrificial anode material layer.
[0018] According to the above-mentioned configuration, in a brazing sheet coated with a brazing material layer and a sacrificial anode material layer, or in a brazing sheet coated only with a sacrificial anode material layer, only the core material contains copper within a predetermined range, and each layer other than the core material does not substantially contain copper. As a result, when the sacrificial anode material layers of the brazing sheet are joined together, copper does not segregate in the fillet formed adjacent to the joint as in the conventional method, but diffuses to concentrate at a suitable concentration, and copper does not substantially diffuse into the sacrificial anode material layer other than the fillet.
[0019] Therefore, in the fillet, the excessive reduction in potential caused by the concentrated zinc is reduced or offset by the diffused copper. This allows the fillet to function as a good sacrificial anode. In addition, since almost no copper diffuses into the sacrificial anode material layer other than the fillet, copper does not interfere with the appropriate reduction in potential caused by zinc, allowing the fillet to function as a good sacrificial anode.
[0020] As a result, the conventional problem of copper segregation reducing the corrosion priority of the surrounding sacrificial anode layer is avoided, and the risk of corrosion progressing from the fillet to the joint, which leads to a decrease in the joint strength, can be effectively suppressed or prevented, thereby making it possible to further improve the corrosion resistance of the joint of the heat exchanger.
[0021] The present invention also includes a heat exchanger having the brazing sheet joint structure described above. Effect of the Invention
[0022] In the present invention, with the above-mentioned configuration, even if a fillet formed adjacent to the joint between brazing sheets contains copper and zinc, it is possible to effectively suppress or prevent preferential corrosion of the fillet, thereby improving the corrosion resistance of the heat exchanger. [Brief description of the drawings]
[0023] [Figure 1] FIG. 1A is a schematic cross-sectional view showing the general configuration of a brazing sheet according to a representative embodiment of the present invention, and FIG. 1B is a schematic cross-sectional view showing the general configuration of the joining structure of a brazing sheet according to a representative embodiment of the present invention. [Diagram 2] FIG. 2A is a schematic cross-sectional view showing an example of a header of a plate-fin stacked type heat exchanger constructed using the brazing sheet shown in FIG. 1, and FIG. 2B is a schematic partial cross-sectional view showing an enlarged bonding structure of the brazing sheet of the header shown in FIG. [Diagram 3] FIG. 2A is a schematic partial cross-sectional view showing an example of a parallel flow capacitor (PFC) constructed using the brazing sheet shown in FIG. 1, and FIG. 2B is a schematic partial cross-sectional view showing an enlarged joint structure of the brazing sheet of the PFC shown in FIG. [Figure 4] FIG. 1A is a schematic cross-sectional view showing an example of a header of a plate-fin stacked type heat exchanger constructed using a brazing sheet having sacrificial anode material layers on both sides, and FIG. 1B is a schematic partial cross-sectional view showing an enlarged joint structure of the brazing sheet of the header shown in FIG. [Diagram 5] FIG. 1 is a diagram showing a cross-sectional photograph of a joint structure of a brazing sheet as a representative embodiment of the present invention, and a graph showing the results of line analysis of the joint structure by an electron probe microanalyzer (EPMA). [Figure 6] FIG. 2 is a diagram showing a cross-sectional photograph of a joint structure of a brazing sheet as a comparative example of the present invention, and a graph showing the results of line analysis of the joint structure by EPMA. [Figure 7] FIG. 2A is a diagram showing the results of a corrosion resistance test of the joint structure of the brazing sheet according to Example 1, and FIG. 2B is a diagram showing the results of a corrosion resistance test of the joint structure of the brazing sheet according to the comparative example. [Figure 8] 1 is a graph showing the comparative relationship between the copper concentration in the core material and the copper concentration in the joint of the brazing sheet according to the present invention. [Figure 9] FIG. 13 is a diagram showing the results of a corrosion resistance test of the joint structure of the brazing sheet according to Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] A brazing sheet according to the present disclosure is a brazing sheet used in a heat exchanger, comprising: an aluminum alloy core material; a brazing material layer coated on one side of the core material and made of a brazing material of an aluminum alloy containing silicon (Si); and a sacrificial anode material layer coated on the other side of the core material and made of a sacrificial anode material of an aluminum alloy containing zinc (Zn) in the range of 0.5 to 6.0 mass % and silicon (Si) in the range of 3.0 to 11 mass %, wherein the brazing sheet has joining surfaces which are joined to each other to form a joint, and non-joining adjacent surfaces which are adjacent to the joining surfaces, the joining surfaces being the sacrificial anode material layer, and when the joining surfaces are joined together, a fillet is formed in which the sacrificial anode material has flowed out from the joining surfaces and solidified, and neither the brazing material nor the sacrificial anode material contains copper (Cu), and the core material contains copper (Cu) in the range of 0.3 to 1.2 mass %.
[0025] Alternatively, the brazing sheet according to the present disclosure may be a brazing sheet used in a heat exchanger, comprising: an aluminum alloy core material; and a sacrificial anode material layer coated on both sides of the core material and made of an aluminum alloy sacrificial anode material containing zinc (Zn) in the range of 0.5 to 6.0 mass% and silicon (Si) in the range of 3.0 to 11 mass%, wherein the brazing sheet has joining surfaces which are joined to each other to form a joint, and non-joining adjacent surfaces which are adjacent to the joining surfaces, the joining surfaces being the sacrificial anode material layer, and when the joining surfaces are joined together, a fillet is formed in which the sacrificial anode material has flowed out from the joining surfaces and solidified at a portion between the non-joining adjacent surfaces and adjacent to the joining surfaces, and the sacrificial anode material does not contain copper (Cu), and the core material contains copper (Cu) in the range of 0.3 to 1.2 mass%.
[0026] According to the above-mentioned configuration, in a brazing sheet coated with a brazing material layer and a sacrificial anode material layer, or in a brazing sheet coated only with a sacrificial anode material layer, only the core material contains copper within a predetermined range, and each layer other than the core material does not substantially contain copper. As a result, when the sacrificial anode material layers of the brazing sheet are joined together, copper does not segregate in the fillet formed adjacent to the joint as in the conventional method, but diffuses to concentrate at a suitable concentration, and copper does not substantially diffuse into the sacrificial anode material layer other than the fillet.
[0027] Therefore, in the fillet, the excessive reduction in potential caused by the concentrated zinc is reduced or offset by the diffused copper. This allows the fillet to function as a good sacrificial anode. In addition, since almost no copper diffuses into the sacrificial anode material layer other than the fillet, copper does not interfere with the appropriate reduction in potential caused by zinc, allowing the fillet to function as a good sacrificial anode.
[0028] As a result, the conventional problem of copper segregation reducing the corrosion priority of the surrounding sacrificial anode layer is avoided, and the risk of corrosion progressing from the fillet to the joint, which leads to a decrease in the joint strength, can be effectively suppressed or prevented, thereby making it possible to further improve the corrosion resistance of the joint of the heat exchanger.
[0029] In the brazing sheet having the above-mentioned configuration, the core material may be an aluminum alloy of any one of 3000 series, 5000 series, or 6000 series to which copper has been added within the above-mentioned range, and the sacrificial anode material layer may be an aluminum alloy of 4000 series to which zinc has been added within the above-mentioned range.
[0030] In the brazing sheet having the above configuration, the brazing material layer may be made of a 4000 series aluminum alloy.
[0031] In the brazing sheet having the above configuration, when the joining surfaces are joined together, the angle formed by the respective non-joint adjacent surfaces may be an acute angle.
[0032] The brazing sheet joint structure according to the present disclosure is used in components constituting a heat exchanger, and is a joint structure in which brazing sheets are joined together, each having an aluminum alloy core material coated with a sacrificial anode material layer made of a sacrificial anode material on at least one surface thereof, the brazing sheets having a joint surface and a non-joining adjacent surface adjacent to the joint surface, each of the joint surfaces being the sacrificial anode material layer, and a fillet formed of the sacrificial anode material that has flowed out from the joint surface and solidified between the non-joining adjacent surfaces, the fillet containing 2.0 mass % or less copper (Cu), which is a concentration that exceeds that of the core material and the sacrificial anode material layer.
[0033] In the brazing sheet joining structure having the above configuration, the sacrificial anode material is an aluminum alloy containing zinc (Zn) in the range of 0.5 to 6.0 mass% and silicon (Si) in the range of 3.0 to 11 mass%, and the core material before joining contains copper (Cu) in the range of 0.3 to 1.2 mass%, and the sacrificial anode material before joining does not contain copper.
[0034] In addition, in the joining structure of the brazing sheet having the above-mentioned configuration, when the sacrificial anode material layer is coated on only one side of the core material, the other side may be coated with a brazing material layer made of a brazing material.
[0035] In the brazing sheet joint structure having the above-described configuration, the brazing material may be an aluminum alloy containing silicon (Si), and the brazing material before joining may not contain copper.
[0036] In the brazing sheet joint structure having the above configuration, the fillet may contain zinc (Zn), and the concentration of copper (Cu) in the fillet may be higher than the concentration of zinc.
[0037] In the brazing sheet joint structure having the above-mentioned configuration, the angle formed by each of the non-joint adjacent surfaces may be an acute angle.
[0038] The heat exchanger according to the present disclosure has the brazing sheet bonding structure described above. Specifically, for example, a plate-fin stacked type heat exchanger or a parallel flow condenser (PFC) can be mentioned.
[0039] Hereinafter, a representative embodiment of the present invention will be described with reference to the drawings. In the following, the same or corresponding elements are denoted by the same reference numerals throughout the drawings, and duplicated descriptions thereof will be omitted.
[0040] [Brazing sheet] The brazing sheet according to the present disclosure is made of an aluminum alloy used in heat exchangers. Specifically, for example, as shown in Fig. 1(A), the brazing sheet 10 according to the present disclosure includes a core material 11, a brazing material layer 12, and a sacrificial anode material layer 13. The brazing material layer 12 is clad on one side of the core material 11, and the sacrificial anode material layer 13 is clad on the other side of the core material 11, i.e., the side opposite to the side on which the brazing material layer 12 is clad. The core material 11, the brazing material constituting the brazing material layer 12, and the sacrificial anode material constituting the sacrificial anode material layer 13 are all aluminum alloys.
[0041] Alternatively, although not shown, the brazing sheet 10 according to the present disclosure may have a configuration including a core material 11 and a sacrificial anode material layer 13, but not including a brazing material layer 12. In such a brazing sheet 10, the sacrificial anode material layer 13 is formed on both surfaces of the core material 11.
[0042] The brazing sheet 10 according to the present disclosure has a joining surface at least on the side of the sacrificial anode material layer 13, and a joint is formed by joining these joining surfaces together. The structure in which the brazing sheets 10 are joined together at their joining surfaces is the joint structure of the brazing sheet 10 according to the present disclosure. The brazing sheet 10 according to the present disclosure has non-joining adjacent surfaces adjacent to the joining surfaces. When the brazing sheets 10 are joined together to form a joint structure, the angle formed by each of the non-joining adjacent surfaces is an acute angle.
[0043] Specifically, for example, as shown in Fig. 1(B), a joint structure 20 of a brazing sheet 10 according to the present disclosure is formed by joining joint surfaces 10a of the brazing sheet 10, and the angle θ1 formed by the non-joined adjacent surfaces 10b adjacent to the joint surfaces 10a is not particularly limited, but a preferred example is an acute angle, i.e., less than 90° (θ1<90°). For convenience of explanation, the angle θ1 formed by each non-joined adjacent surface 10b constituting the joint structure 20 is referred to as the "adjacent surface angle" and is shown by a dotted line in Fig. 1(B).
[0044] As described above, the preferred range of the adjacent surface angle θ1 is not particularly limited as long as it is an acute angle, i.e., less than a right angle (less than 90°), but depending on various conditions such as the type of heat exchanger and the structure of the heat exchanger in which the brazing sheet 10 is used, it may be, for example, within the range of 40° to 80° (40°≦θ1≦80°) or may be within the range of 50° to 70° (50°≦θ1≦70°). Alternatively, for example, only the lower limit may be 15° or more (15°≦θ1) or 20° or more (20°≦θ1).
[0045] In the joint structure 20 according to the present disclosure, when the brazing sheets 10 are joined together to form a joint 21, a fillet 22 is formed between the non-joined adjacent surfaces 10b as shown in Fig. 1(B). The heat exchanger includes a member or structure in which such a fillet 22 is formed, and in such a member or structure, the non-joined adjacent surfaces 10b often form an acute angle. In this embodiment, this fillet 22 is defined as the brazing material (or sacrificial anode material) that flows out from the joining surfaces 10a during joining and solidifies.
[0046] The present disclosure effectively suppresses or avoids preferential corrosion of the fillet 22 in a heat exchanger using the brazing sheet 10. If the adjacent surface angle θ1 becomes too large, for example, approaching 180°, i.e., horizontal, the fillet 22 is structurally difficult to form. If the adjacent surface angle θ1 is too small, the non-joint adjacent surfaces 10b become closer to being parallel, and the fillet 22 is difficult to form, although this depends on the structure of the heat exchanger, etc. Therefore, a suitable example of the adjacent surface angle θ1 is an angle within the range of the above-mentioned upper and lower limits, or an angle equal to or greater than the lower limit.
[0047] In the brazing sheet 10 according to the present disclosure, it is sufficient that the joining surface 10a is set at least on the sacrificial anode material layer 13. Therefore, as described later, the sacrificial anode material also serves as a brazing material. That is, the sacrificial anode material layer 13 contributes to the joining of the brazing sheets 10 as a brazing material during joining, and contributes to the anticorrosive effect of the brazing sheets 10 as a sacrificial anode material after joining.
[0048] In the brazing sheet 10 according to the present disclosure, a non-adjacent surface 10b is set adjacent to the joining surface 10a. Therefore, the non-adjacent surface 10b is also a sacrificial anode material layer 13, like the joining surface 10a. As described above, when the brazing sheets 10 are joined together, the non-adjacent surfaces 10b form an angle (adjacent surface angle θ1) that is, for example, an acute angle. Therefore, for example, as shown in FIG. 1(B), the non-adjacent surface 10b may be inclined with respect to the joining surface 10a.
[0049] In the example shown in Fig. 1(B), the non-bonded adjacent surfaces 10b are inclined to form an angle θ2 with respect to the bonding surface 10a. Therefore, when the bonding surfaces 10a are bonded to each other to form the bonded portion 21, the non-bonded adjacent surfaces 10b adjacent to each bonding surface 10a form an acute adjacent surface angle θ1. For convenience of explanation, the inclination angle θ2 of the non-bonded adjacent surfaces 10b with respect to the bonding surface 10a is referred to as the "adjacent surface inclination angle" and is shown in Fig. 1(B) by a dotted line together with an extension of the bonding surface 10a.
[0050] The specific angle of the adjacent surface inclination angle θ2 is not particularly limited, but for example, as shown in FIG. 1(B), if the shapes of the brazing sheets 10 to be joined to each other are line-symmetrical with respect to the joining surface 10a, the adjacent surface formation angle θ1 is twice the adjacent surface inclination angle θ2 (θ1=θ2×2). Therefore, if the adjacent surface formation angle θ1 is an acute angle, the adjacent surface inclination angle θ2 may be less than 45°. However, the shape of the brazing sheet 10 does not need to be line-symmetrical, and brazing sheets 10 of various shapes will be joined to each other at the joining surface 10a depending on various conditions such as the type of heat exchanger or the structure of the heat exchanger. In addition, the adjacent surface formation angle θ1 does not necessarily need to be an acute angle. Therefore, the adjacent surface inclination angle θ2 is not limited to less than 45°.
[0051] For example, a joining structure 20 may be possible in which brazing sheets 10 of different shapes are joined in a state of being inclined with respect to the joining surface 10a of a substantially flat brazing sheet 10. In this case, the non-joining adjacent surfaces 10b of the substantially flat brazing sheet 10 are not inclined with respect to the joining surface 10a, and are set as different regions on the sacrificial anode material layer 13. Therefore, the adjacent surface inclination angle θ2 may be 0° (θ2=0°). In other words, the non-joining adjacent surfaces 10b are not inclined with respect to the joining surface 10a, and may be different regions of a continuous flat surface (see the joining structure of a parallel flow capacitor described later).
[0052] In the joint structure 20 of the brazing sheet 10 according to the present disclosure, corrosion may progress in the directions indicated by block arrows C1 and C2 in Fig. 1(B). The direction of block arrow C1 is the corrosion direction that progresses from the non-joint adjacent surface 10b (and the non-joint surface that is not adjacent to the joint surface 10a) toward the core material 11, and the direction of block arrow C2 is the corrosion direction that progresses along the direction of the joint surface 10a in the joint 21 including the fillet 22.
[0053] Of these, corrosion that progresses in corrosion direction C1 is suppressed (avoided or prevented) by the sacrificial anode action of the sacrificial anode material layer 13, but corrosion that progresses in corrosion direction C2 may progress because the potential of the joint 21 including the fillet 22 becomes too noble due to zinc being concentrated in the fillet 22. In the brazing sheet 10 according to the present disclosure, the core material 11 contains copper within a predetermined range, and the brazing material layer 12 and the sacrificial anode material layer 13 are substantially free of copper, thereby making it possible to effectively suppress (avoid or prevent) corrosion in the corrosion direction C2.
[0054] [Brazing sheet material] The brazing sheet 10 according to the present disclosure is made of an aluminum alloy as described above, and the core material 11, the brazing material, and the sacrificial anode material are all made of aluminum alloys. Specifically, the core material 11 may be any known aluminum alloy capable of achieving the physical properties required according to various conditions such as the type or structure of the heat exchanger, but in the present disclosure, copper (Cu) is added (contained) in the range of 0.3 to 1.2 mass %.
[0055] In the field of heat exchangers, typical examples of aluminum alloys used as the core material 11 include, but are not limited to, 3000 series (aluminum-manganese (Al-Mn) alloys), 5000 series (aluminum-magnesium (Al-Mg) alloys), and 6000 series (aluminum-magnesium-silicon (Al-Mg-Si) alloys). In the present disclosure, these aluminum alloys or other aluminum alloys may be used as the core material 11 by adding Cu to the above-mentioned range by a known method.
[0056] For convenience, the aluminum alloy before adding Cu is called the "base material." In the base material, Cu may be contained in advance as an inevitable impurity. Even if Cu is contained as an inevitable impurity, the concentration may be, for example, 0.2 mass% or less. However, aluminum alloys that already contain Cu at a concentration exceeding 1.2 mass%, such as 2000 series alloys, cannot be used as the base material for the core material 11.
[0057] In the brazing sheet 10 according to the present disclosure, if the Cu content (concentration) in the core material 11 is less than 0.3 mass %, as described below, there is a risk that Cu will not diffuse in a sufficient concentration from the core material 11 to the fillet 22. Furthermore, if the Cu content in the core material 11 exceeds 1.2 mass %, the susceptibility of the core material 11 to intergranular corrosion will increase, and the progress of corrosion may not be effectively suppressed, although this depends on the strength of the sacrificial anode action of the sacrificial anode material.
[0058] The Cu content in the core material 11 may be within a range of 0.3 to 1.2 mass%, and a preferred example is within a range of 0.3 to 0.7 mass%. That is, the upper limit of the Cu content may be 1.2 mass% or less, and may be 0.7 mass% or less depending on various conditions. If the Cu content is 0.7 mass% or less, the risk of the core material 11 becoming highly susceptible to intergranular corrosion can be effectively suppressed even if the sacrificial anode action of the sacrificial anode material is relatively weak.
[0059] In the present disclosure, the aluminum alloy used as the brazing material may contain silicon (Si), that is, may be an aluminum-silicon (Al-Si) alloy. The content (concentration) of Si in the brazing material is not particularly limited, and may be within a range that allows suitable use as a brazing material. Specifically, for example, the content of Si in the brazing material may be within a range of 2.5 to 13 mass%, or may be within a range of 3.5 to 12 mass%. If the content of Si is too low, the Al-Si alloy may not function sufficiently as a brazing material. On the other hand, if the content of Si is too high, Si may diffuse into the core material 11 or the mating material, causing the brazing sheet 10 itself to melt.
[0060] The Al-Si alloy as a brazing material may contain elements other than Si as long as the function as the brazing material is not affected. The Al-Si alloy as a brazing material may contain various elements as unavoidable impurities. However, the Al-Si alloy as a brazing material does not substantially contain Cu. Substantially not containing Cu means that Cu is not contained at a concentration exceeding the unavoidable impurities. The upper limit of the concentration allowed as an unavoidable impurity varies depending on various conditions, but generally, it can be less than 0.1 mass% in the entire Al-Si alloy.
[0061] The aluminum alloy used as the sacrificial anode material contains zinc (Zn) in the range of 0.5 to 6.0 mass % in order to exert a sacrificial anode function. In addition, in the present disclosure, since the sacrificial anode material also serves as a brazing material as described above, it contains Si like the brazing material. The sacrificial anode material may have a Si content in the range of 3.0 to 11 mass %. Therefore, the aluminum alloy used as the sacrificial anode material may be an aluminum-silicon-zinc (Al-Si-Zn) based alloy.
[0062] In the Al-Si-Zn alloy as the sacrificial anode material, if the Zn content (concentration) is less than 0.5 mass%, the sacrificial anode function cannot be satisfactorily exhibited. On the other hand, if the Zn content exceeds 6.0 mass%, the sacrificial anode function will proceed too early, causing the sacrificial anode material layer 13 to disappear early from the brazing sheet 10, and the corrosion resistance of the brazing sheet 10 may decrease.
[0063] Furthermore, if the Al-Si-Zn alloy as the sacrificial anode material contains too little or too much Si, it cannot be used appropriately as a brazing material as described above. In particular, in the present disclosure, if the Si content is within the range of 3.0 to 11 mass %, the sacrificial anode material layer 13 can be provided with a satisfactory function as a brazing material without substantially affecting the sacrificial anode function.
[0064] The Al-Si-Zn alloy as the sacrificial anode material may contain elements other than Si and Zn, as long as they do not affect the sacrificial anode action and the function as the brazing material. The Al-Si-Zn alloy as the sacrificial anode material may contain various elements as unavoidable impurities. However, the Al-Si-Zn alloy as the sacrificial anode material does not substantially contain Cu. The term "substantially not containing Cu" means that, as with the Al-Si alloy as the brazing material, Cu is not contained at a concentration exceeding the unavoidable impurities, and generally, the concentration may be less than 0.1 mass% in the entire Al-Si-Zn alloy. Alternatively, the upper limit of the concentration of the unavoidable impurities may conform to the alloy composition specified in a known standard such as JIS.
[0065] The type of aluminum alloy specifically used as the brazing material and the sacrificial anode material is not particularly limited, but typically, 4000 series (aluminum-silicon (Al-Si) alloy) can be used for both. The sacrificial anode material may be a 4000 series aluminum alloy to which Zn has been added by a known method so that the content is within the range of 0.5 to 6.0 mass%.
[0066] In the brazing sheet 10 according to the present disclosure, the cladding ratio of the brazing material and the sacrificial anode material is not particularly limited and may be within a general range. A general cladding ratio may be, for example, within a range of 2 to 30 mass%, and may be within a range of 3 to 20 mass%. In addition, the thickness of the brazing sheet 10 and the thicknesses of the core material 11, the brazing material layer 12, and the sacrificial anode material layer 13 are not particularly limited and may be appropriately set depending on the configuration of the brazing sheet 10 or the type or parts of the heat exchanger to be manufactured.
[0067] In the present disclosure, the brazing sheets 10 are joined together by overlapping multiple brazing sheets 10 with their joining surfaces 10a facing each other and melting the brazing material and sacrificial anode material at a high temperature (580°C or higher) to braze the brazing sheets 10. In the joint structure 20 of the brazing sheets 10 thus manufactured, as shown in Fig. 1(B) , in the portion adjacent to the joining surface 10a (joint 21) between the non-joined adjacent surfaces 10b, the sacrificial anode material that has flowed out from the sacrificial anode material layer 13 of the joining surface 10a solidifies to form a fillet 22.
[0068] This fillet 22 contains Zn because it is formed from the sacrificial anode material that has flowed out from the joining surface 10a, but it also contains Cu that has diffused from the core material 11. The Cu concentration in the fillet 22 (joint 21) exceeds that in the core material 11, the brazing material layer 12, and the sacrificial anode material layer 13, and exhibits a concentration distribution in which Cu is substantially localized in the fillet 22. From the results of the examples and comparative examples described below, when the Cu concentration in the core material 11 is within a predetermined range and the brazing material layer 12 and the sacrificial anode material layer 13 contain substantially no Cu, Cu behaves in a manner such that it locally concentrates and diffuses from the core material 11 to the fillet 22 (joint 21) during joining at high temperatures.
[0069] Zn behaves in such a way that it diffuses into the joint 21 (fillet 22) during the process in which the sacrificial anode material (brazing filler metal) melts from the sacrificial anode material layer 13 to form the fillet 22. Therefore, although the Zn concentration in the fillet 22 is highest in the joint 21, Zn also remains in the sacrificial anode material layer 13. Therefore, in a cross section in the thickness direction of the joint 21 including the fillet 22, the Cu concentration shows a parabolic distribution with a maximum value at the fillet 22 (see Examples and Comparative Examples described later). In contrast, Cu does not behave like Zn and tends to diffuse so as to be locally concentrated as the fillet 22 is formed, and Cu is significantly less than Zn or is barely detectable in both the sacrificial anode material layer 13 and the core material 11 (see Examples described later).
[0070] In the joint structure 20 of the brazing sheet 10 according to the present disclosure, the Cu concentration and Zn concentration in the fillet 22 are not particularly limited, but the Cu concentration may be 2.0 mass% or less, and the Zn concentration may be less than the Cu concentration. If the Cu concentration in the fillet 22 exceeds 2.0 mass%, aging precipitation of an intermediate compound phase containing Cu occurs in a short period of time compared to the life of the heat exchanger. Such precipitates function as a cathode in the corrosion reaction, so that the corrosion current density in the fillet 22 increases, and the corrosion resistance around the fillet 22 may be significantly deteriorated.
[0071] As described later, a proportional relationship is observed between the Cu concentration (initial Cu concentration) of the core material 11 and the Cu concentration of the joint 21 (fillet 22) in the joint structure 20. Therefore, if the Cu concentration of the core material 11 is 1.2 mass% or less, the Cu concentration of the fillet 22 is considered to be 2.0 mass% or less. On the other hand, the Cu concentration of the core material 11 may be 0.3 mass% or more, and in this case, the Cu concentration of the fillet 22 in the joint structure 20 is considered to be 0.5 mass% or more. Therefore, the lower limit of the Cu concentration of the fillet 22 in the joint structure 20 may be equal to or greater than the Zn concentration, but is preferably equal to or greater than 0.5 mass%.
[0072] As mentioned above, the core material also contains Cu in the range of 0.05 to 1.2 mass% in the conventional brazing sheet disclosed in Patent Document 2, but the brazing sheet also contains Cu in the range of 0.1 to 0.6 mass%. For this reason, it is believed that the brazing sheet disclosed in Patent Document 2 does not behave in such a way that Cu locally concentrates from the core material to the fillet during joining at high temperatures, as in the present disclosure.
[0073] In the present disclosure, it is considered that Cu of the core material 11 diffuses into the sacrificial anode material due to high heat during joining, and the molten sacrificial anode material (functioning as a brazing material) flows into the joint 21 to form the fillet 22, and Cu concentrates on the fillet 22. In this way, the concentration of Cu on the fillet 22 makes the potential of the joint 21 around the fillet 22 more noble than the surroundings. However, according to the present disclosure, unlike the conventional brazing sheet, the potential of the joint 21 is not made too noble by Cu, and it is possible to suppress or avoid the reduction of the sacrificial anode action by Zn. As a result, the deterioration of the corrosion resistance of the joint 21 including the fillet 22 is also suppressed or avoided, and it is possible to improve the corrosion resistance life of a heat exchanger having such a joint structure 20.
[0074] Moreover, Cu remains in the core material 11 in the areas other than the joint 21. When the core material 11 contains Cu within a predetermined range, the core material 11 becomes nobler, and the potential difference with the sacrificial anode material layer 13 can be increased. This allows the sacrificial anode action of the sacrificial anode material layer 13 to be more effectively exerted. Furthermore, by adding Cu to the core material 11, the strength of the core material 11 can be improved. This is advantageous for making the brazing sheet 10 thinner and improving the pressure resistance of the heat exchanger.
[0075] As a method for suppressing or avoiding preferential corrosion of the joint without including Cu in the joint, it is possible to isolate the joint from the surroundings by painting or partially removing the sacrificial anode material layer. However, such a method requires an additional step of painting or partially removing the sacrificial anode material layer, which increases the manufacturing cost, makes the entire manufacturing process complicated, and in the case of painting, causes problems such as peeling and scattering of the paint film. In contrast, in the present disclosure, Cu can be appropriately concentrated in the fillet 22 simply by including Cu in the core material 11 and joining it, so no additional step is required and easy manufacturing is possible.
[0076] Furthermore, the method for evaluating the potential of the joint 21 including the fillet 22, the sacrificial anode material layer 13, etc. is not particularly limited, and a known method can be suitably used. A representative example is a method in which a sample for potential measurement (for example, the brazing sheet 10, or the core material 11, the brazing material, the sacrificial anode material, the fillet 22 or the joint 21, or an alloy having a composition simulating these, etc.), a counter electrode, and a reference electrode (for example, a silver / silver chloride (Ag / AgCl) electrode) are connected to a potentiostat / galvanostat, and the sample is immersed in an electrolyte (for example, a 5 wt.% sodium chloride (NaCl) solution), and the potential difference between the sample and the reference electrode is measured.
[0077] The method for manufacturing the brazing sheet 10 according to the present disclosure is not particularly limited, and a known manufacturing method can be suitably used. Specifically, for example, an aluminum alloy containing Cu in the range of 0.3 to 1.2 mass% is formed into a plate shape by a known method to form the core material 11, one side of the core material 11 is clad with a brazing material of an aluminum alloy containing Si by a known method, and the other side of the core material 11 is clad with a sacrificial anode material of an aluminum alloy containing Zn in the range of 0.5 to 6.0 mass% and Si in the range of 3.0 to 11 mass% by a known method. In the present disclosure, the various conditions for manufacturing the brazing sheet 10 can be appropriately set depending on the configuration of the brazing sheet 10 or the type or parts of the heat exchanger to be manufactured.
[0078] [Brazing sheet joint structure and heat exchanger] The brazing sheet 10 according to the present disclosure can be particularly suitably used for manufacturing a heat exchanger, as described above. The joint structure 20 formed when the brazing sheet 10 according to the present disclosure is applied to a heat exchanger is, as described above, a structure as exemplified in Fig. 1(B), but more specifically, examples of the joint structure include a plate-fin stacked type heat exchanger having a structure as shown in Figs. 2(A) and (B), a parallel flow condenser (PFC) having a structure as shown in Figs. 3(A) and (B), and a stacked type heat exchanger for an air-to-water heat pump having a structure as shown in Figs. 4(A) and (B).
[0079] Although not shown, a plate fin stack type heat exchanger is a plate fin stack having flow paths through which a first fluid, a refrigerant, flows a second fluid, air, between the plate fin stacks to exchange heat between the first and second fluids. The plate fins of this heat exchanger have a flow path region having multiple first fluid flow paths through which the first fluid flows in parallel, and a header region having header flow paths communicating with each of the first fluid flow paths in the flow path region.
[0080] In a plate fin stack type heat exchanger, end plates having approximately the same shape as the plate fins in a plan view are provided on both sides of the plate fin stack in the stacking direction, and this pair of end plates and the multiple plate fins between them are joined together by brazing in a stacked state to form an integrated unit. Figure 2(A) shows a partial cross section of the schematic structure of the header portion of this plate fin stack 30, with multiple plate fins 32 stacked on an end plate 31 located at the top of the figure.
[0081] The end plates 31 and the plate fins 32 each have an opening, and these plates are stacked to form the plate fin stack 30, thereby forming the header opening 33. In the configuration shown in FIG. 2(A), a coolant, which is a first fluid, flows in from the outside of the header opening 33 in the direction indicated by the block arrow in the figure, and further flows between the plate fins 32. Since each plate fin 32 is provided with a first fluid flow path as described above, the coolant that flows between the plate fins 32 flows through the first fluid flow path. In addition, air, which is a second fluid, flows through the space formed between the plate fins 32 in a manner that crosses the direction in which the coolant flows (the direction of the first fluid flow path). As a result, the air is cooled by the coolant.
[0082] Fig. 2(B) is a partially enlarged view of the plate fin stack 30 shown in Fig. 2(A), and shows a schematic example of a joint structure 20 of the brazing sheet 10 according to the present disclosure. In the example shown in Figs. 2(A) and (B), the plate fin 32 is the brazing sheet 10 according to the present disclosure, and the joint structure 20 according to the present disclosure is a joint 21 located on the header opening 33 side. In Fig. 2(B), the plate fin 32 which is the brazing sheet 10 is shown with the sacrificial anode material layer 13 highlighted by hatching, and the fillet 22 is also shown with hatching highlighted.
[0083] At the joint 21 on the header opening 33 side, the joint surfaces 10a of the plate fins 32 are joined together, and a fillet 22 is formed between the non-joint adjacent surfaces 10b adjacent to the joint surfaces 10a. In the present disclosure, the core material 11 of the plate fin 32 contains Cu in the range of 0.3 to 1.2 mass %, and the brazing material layer 12 and the sacrificial anode material layer 13 of the plate fin 32 do not substantially contain Cu. Therefore, the fillet 22 contains Cu at a concentration higher than that of the core material 11, the brazing material layer 12, and the sacrificial anode material layer 13, and contains 2.0 mass % or less of Cu. This effectively suppresses (avoids or prevents) preferential corrosion of the joint 21, thereby improving the corrosion resistance life of the plate fin stacked heat exchanger.
[0084] Specific configuration examples of such plate fin stacked type heat exchangers are described in, for example, JP 2017-180856 A, JP 2018-066531 A, JP 2018-066532 A, JP 2018-066533 A, JP 2018-066534 A, JP 2018-066535 A, JP 2018-066536 A, etc., and the contents of these publications are incorporated herein by reference as part of the description of this specification.
[0085] In the joint structure 20 shown in FIG. 2(B), the plate fin 32, which is the brazing sheet 10, has a two-stage bend. That is, the non-joint adjacent surface 10b is inclined to the joint surface 10a on the right side in the figure so as to form an acute adjacent surface inclination angle θ2, and further, on the left side of the non-joint adjacent surface 10b, there is a non-joint surface parallel to the joint surface 10a. However, the specific shape of the brazing sheet 10 is not limited to such a shape having two stages of bends, and may be a flat shape without a bend, a shape having one stage of bend as shown in FIG. 1(B), a shape having three or more stages of bends, or a shape having other three-dimensional structures such as curved parts. The specific shape of the brazing sheet 10 is appropriately set depending on various conditions such as the type or structure of the heat exchanger.
[0086] A parallel flow condenser (PFC) is a heat exchanger widely used for car air conditioners (automotive air conditioners), in which a plurality of flat tubes are arranged between a pair of header tubes, and corrugated fins for heat dissipation are arranged between these flat tubes. These header tubes, flat tubes, corrugated fins, etc. are joined by brazing. FIG. 3(A) shows a schematic structure of a connection portion between a header tube 41 and flat tubes 42 in this PFC 40 as a partial cross section. Corrugated fins 43 are provided between the flat tubes 42, and these are also joined by brazing, but the joint structure 20 according to the present disclosure is the connection portion between the header tube 41 and the flat tubes 42, as shown in an enlarged view in FIG. 3(B).
[0087] 3(B), the header tube 41 and the flat tube 42 are both brazing sheets 10, and the header tube 41 and the flat tube 42 are illustrated with the sacrificial anode material layer 13 emphasized by hatching. The fillet 22 is also illustrated with the fillet 22 emphasized by hatching. Since the sacrificial anode material layer 13 of the flat tube 42 is flat, the joining surface 10a and the non-joining adjacent surface 10b are set as different regions on a continuous single surface (the surface of the sacrificial anode material layer 13). Therefore, the flat tube 42 is a brazing sheet 10 having a flat shape with no bends.
[0088] The header pipe 41 has an opening for inserting the flat tubes 42 therethrough, and this opening is provided with a joint surface 10a and a non-joint adjacent surface 10b. In Fig. 3(B) , the joint surface 10a of the header pipe 41 is illustrated as a surface that is parallel to the joint surface 10a (outer surface) of the flat tubes 42, but is not limited thereto, and may be a surface that is not parallel to the outer surface of the flat tubes 42. The opening of the header pipe 41 has a shape with a one-stage bend in the brazing sheet 10.
[0089] In the joint structure 20 shown in FIG. 3(B), a fillet 22 is formed between the non-joint adjacent surface 10b adjacent to the joint surface 10a of the header tube 41 and the non-joint adjacent surface 10b adjacent to the joint surface 10a of the flat tube 42. In the present disclosure, the core material 11 of the header tube 41 and the flat tube 42 contains Cu in the range of 0.3 to 1.2 mass%, and the brazing material layer 12 and the sacrificial anode material layer 13 of the header tube 41 and the flat tube 42 do not substantially contain Cu. Therefore, the fillet 22 contains Cu at a concentration exceeding that of the core material 11, the brazing material layer 12, and the sacrificial anode material layer 13, and is 2.0 mass% or less. This effectively suppresses (avoids or prevents) preferential corrosion of the joint 21, thereby improving the corrosion resistance life of the plate-fin stacked heat exchanger.
[0090] The manufacturing method of the joint structure 20 of the brazing sheet 10 is not particularly limited, and a known brazing method or the like can be suitably used. For example, a method of applying a known flux to the joint surface 10a of the brazing sheet 10 and then heating it in a nitrogen atmosphere furnace at a temperature of, for example, about 600°C can be used. In particular, in the joint structure 20 according to the present disclosure, the Cu content in the fillet 22 (and the joint portion 21) is not substantially affected by the detailed joining conditions.
[0091] As shown in Fig. 4(A), the plate fin laminate 34 constituting the laminated heat exchanger for an air-to-water heat pump has a basic configuration similar to that of the plate fin laminate 30 of a general plate fin laminated heat exchanger. However, as shown in Fig. 4(B), the plate fins 35 (brazing sheets 10 according to the present disclosure) constituting the plate fin laminate 34 have sacrificial anode material layers 13 on both sides. Therefore, as shown in Figs. 4(A) and (B), the fillets 22 are formed not only at the joints 21 located on the header opening 33 side (inside) but also at the joints 21 located on the opposite side to the header opening 33 side (outside).
[0092] In the present disclosure, the core material 11 of the plate fin 35 contains Cu in the range of 0.3 to 1.2 mass %, and none of the sacrificial anode material layers 13 of the plate fin 35 contains substantially any Cu. Therefore, the fillet 22 contains Cu at a concentration higher than that of the core material 11 and the sacrificial anode material layers 13, that is, 2.0 mass % or less. This effectively suppresses (avoids or prevents) preferential corrosion of the joint 21, thereby improving the corrosion resistance life of the plate fin stacked heat exchanger. Note that the configuration shown in Figures 4(A) and (B) is the same as the configuration shown in Figures 2(A) and (B) except for the positions of the plate fin 35 and the fillet 22, and therefore a description thereof will be omitted.
[0093] Thus, the brazing sheet according to the present disclosure is used in a heat exchanger and comprises an aluminum alloy core material, a brazing material layer of an aluminum alloy containing silicon (Si) coated on one side of the core material, and a sacrificial anode material layer of an aluminum alloy containing zinc (Zn) in the range of 0.5 to 6.0 mass % and silicon (Si) in the range of 3.0 to 11 mass % coated on the other side of the core material, or a sacrificial anode material layer coated on both sides of the core material.
[0094] This brazing sheet has bonding surfaces that form a bonded portion by being bonded together, and non-adjacent bonding surfaces adjacent to the bonding surfaces, the bonding surfaces being sacrificial anode material layers, and when the bonding surfaces are bonded together, fillets are formed in the areas between the non-adjacent bonding surfaces and adjacent to the bonding surfaces by the sacrificial anode material flowing out from the bonding surfaces and solidifying. Neither the brazing material nor the sacrificial anode material contains Cu, and the core material contains Cu in the range of 0.3 to 1.2 mass%.
[0095] The brazing sheet joint structure according to the present disclosure is used in a member constituting a heat exchanger, and is a joint structure in which brazing sheets are joined together, each having an aluminum alloy core material with at least one surface coated with a sacrificial anode material layer (both surfaces may be coated with a sacrificial anode material layer, or the other surface may be coated with a brazing material layer), the brazing sheet has a joint surface and a non-joining adjacent surface adjacent to the joint surface, each joint surface is a sacrificial anode material layer, the angle formed by each non-joining adjacent surface is an acute angle, and a fillet is formed between the non-joining adjacent surfaces and adjacent to the joint surface, the fillet containing Cu that has flowed out from the joint surface and solidified, at a concentration exceeding that of the core material, the brazing material layer, and the sacrificial anode material layer and not more than 2.0 mass %.
[0096] In this configuration, when the brazing sheet is joined with the sacrificial anode material layer, Cu is diffused to concentrate in the fillet formed adjacent to the joint to a suitable concentration, but Cu is not substantially diffused to the sacrificial anode material layer other than the fillet. Therefore, in the fillet, the excessively noble potential caused by the concentrated zinc is reduced or offset by Cu, so that a good sacrificial anode action can be realized in the fillet. In addition, since Cu is hardly diffused to the sacrificial anode material layer other than the fillet, Cu does not hinder the moderate noble potential caused by zinc, so that a good sacrificial anode action can be realized. As a result, the risk of corrosion progressing from the fillet to the joint and causing a decrease in the joint strength can be effectively suppressed or prevented, so that the corrosion resistance of the joint of the heat exchanger can be further improved.
[0097] The present disclosure may also include a method for joining brazing sheets used in members constituting a heat exchanger, the brazing sheet having an aluminum alloy core material with a brazing material layer made of a brazing material on one side and a sacrificial anode material layer made of a sacrificial anode material on the other side. In this joining method, the brazing material is an aluminum alloy containing silicon (Si), the sacrificial anode material is an aluminum alloy containing zinc (Zn) in the range of 0.5 to 6.0 mass% and silicon (Si) in the range of 3.0 to 11 mass%, the core material before joining contains copper (Cu) in the range of 0.3 to 1.2 mass%, and neither the brazing material nor the sacrificial anode material before joining contains copper, the brazing sheet has a joining surface and a non-joining adjacent surface adjacent to the joining surface, each joining surface is a sacrificial anode material layer, the joining surfaces of the brazing sheets are abutted against each other and heated, and the sacrificial anode material flows out from the joining surface and solidifies to form a fillet in the portion between the non-joining adjacent surfaces and adjacent to the joining surface. EXAMPLES
[0098] The present invention will be described in more detail with reference to examples and comparative examples, but the present invention is not limited thereto. Those skilled in the art can make various changes, modifications, and alterations without departing from the scope of the present invention. The evaluation methods of physical properties in the following examples and comparative examples were performed as follows.
[0099] (Evaluation method, etc.) [Joint and non-joint surfaces of brazing sheet] The brazing sheet used was 200 μm thick and had a three-layer structure with a sacrificial anode material layer on one side and a brazing material layer on the other side. The joining surface and non-joining adjacent surface of the brazing sheet were both on the side of the sacrificial anode material layer. The angle of the non-joining adjacent surface with respect to the joining surface differed slightly depending on the brazing sheet, but was basically about 30°±5° (within a range of 25 to 35°), and when the joining surfaces were joined together, the angle formed by the non-joining adjacent surfaces was about 60°±10° (within a range of 50 to 70°).
[0100] [Analysis of elemental concentration in joints] An electron probe microanalyzer (EPMA), model EMPA-1600 manufactured by Shimadzu Corporation, was used to analyze the concentrations of Cu and Zn along the cross-sectional direction of the side of the non-joint adjacent surface at the joint between the brazing sheets (brazing sheet joint structure) under analysis conditions of accelerating voltage: 15 kV, beam diameter: 2 μm, accumulation time: 1 s, step interval: 2 μm, and sample current: 0.15 μA.
[0101] [Corrosion resistance test] The corrosion resistance of the brazing sheet joint structure was evaluated based on the Sea Water Acidified Test (SWAAT) specified in ASTM G85-A3.
[0102] Example 1 In the brazing sheet according to Example 1, an aluminum alloy (Al-1.30%Mn-0.46%Cu) of 1.30% by mass of manganese (Mn), 0.46% by mass of copper (Cu), and the remainder aluminum (Al) was used as the core material, an aluminum alloy (Al-7.49%Si-1.00%Zn) of 7.49% by mass of silicon (Si), 1.00% by mass of zinc (Zn), and the remainder aluminum (Al) was used as the sacrificial anode material, and an aluminum alloy (Al-7.40%Si) of 7.40% by mass of silicon (Si), and the remainder aluminum (Al) was used as the brazing material. Note that the sacrificial anode material contains 7.49% by mass of silicon, and therefore also functions as a brazing material.
[0103] The brazing sheet joint structure of Example 1 was manufactured by brazing two brazing sheets to each other at their joint surfaces to form a joint. The brazing condition was 610°C. As shown in the cross-sectional photograph in the upper part of Fig. 5, the element concentrations of the portion on the non-joined adjacent surface side of this joint, i.e., the fillet, were analyzed by EPMA as described above along the cross-sectional direction indicated by the arrow in the figure.
[0104] As a result, as shown in the line elemental analysis results in the lower diagram of Figure 5, the Zn concentration in the fillet cross section gradually increased from the core side to the joint surface side, showing a parabolic concentration distribution with a maximum (approximately 0.4 wt%) near the joint surface (region 200 μm ± 40 μm). However, the Cu concentration was barely detectable in the braze layer and core side (regions 0 to 140 μm and 260 to 400 μm), and was detected as a strong peak (maximum of 1 wt% or more, and minimum of more than 0.4 wt% (approximately 0.44 wt%)) that suddenly exceeded the zinc concentration near the joint surface of the fillet (region 200 μm ± 40 μm).
[0105] In addition, although not shown in the figure, color mapping, which is the result of surface analysis by EPMA, confirmed that Zn was distributed in low concentration overall, mainly around the fillet, while Cu was found to be present in high concentration near the fillet.
[0106] Furthermore, the corrosion resistance of the joints between the brazing sheets was evaluated by the above-mentioned corrosion test. As a result, as shown in the cross-sectional photograph of Figure 7(A), no substantial corrosion was observed.
[0107] (Comparative Example) In the brazing sheet according to the comparative example, the sacrificial anode material and the brazing material are the same aluminum alloy as the brazing sheet according to the example 1, but the core material is an aluminum alloy (Al-1.10%Mn-0.14%Cu) with 1.10 mass% manganese (Mn), 0.14 mass% copper (Cu), and the remainder aluminum. Note that this Cu concentration is 0.2 mass% or less, which is the content equivalent to the impurity in the core material.
[0108] A brazing sheet joint structure of the comparative example was manufactured by joining two brazing sheets to form a joint in the same manner as in Example 1. As shown in the cross-sectional photograph in the upper diagram of Figure 6, element concentrations were analyzed by EPMA as described above for the region on the non-joined adjacent surface side of this joint along the cross-sectional direction indicated by the arrow in the figure.
[0109] As a result, as shown in the line elemental analysis results in the lower diagram of Figure 6, the Zn concentration shows a parabolic concentration distribution, similar to the joint in Example 1, but for Cu, only two peaks lower than the zinc concentration (a peak of approximately 0.2 weight% near 220 μm and a peak of approximately 0.3 weight% near 230 μm) were observed on the joint side of one of the core materials (region 220 to 240 μm), and no substantial Cu concentration was detected outside of these peaks.
[0110] In addition, although not shown in the figure, color mapping, which is the result of surface analysis by EPMA, confirmed that Zn was distributed in low concentration overall, mainly around the fillet, as in Example 1, but Cu was hardly detected.
[0111] Furthermore, the corrosion resistance of the joint between the brazing sheets was evaluated by the above-mentioned corrosion test. As a result, as shown in the cross-sectional photograph of Figure 7(B), corrosion occurred at the part of the joint on the adjacent surface side.
[0112] Example 2 The brazing sheet according to Example 2 is similar to the brazing sheet according to Example 1, except that it has sacrificial anode material layers on both sides of the core material and does not have brazing material layers. Then, two brazing sheets were joined to form a joint in the same manner as in Example 1, to produce a joint structure of the brazing sheet according to Example 2. In this joint structure, the corrosion resistance of the joint between the brazing sheets was evaluated by the above-mentioned corrosion test. As a result, as shown in the cross-sectional photograph of FIG. 9, substantial corrosion could not be confirmed.
[0113] (Comparison between Examples and Comparative Examples) As is clear from a comparison between Figures 5 and 6, and between Figures 7(A) and (B), if a core material containing only impurity amounts of Cu is used (Comparative Example), Cu does not diffuse so as to concentrate at the fillet, but if a core material containing Cu within a specified range is used (Example 1), Cu diffuses so as to concentrate at the fillet, thereby making it possible to effectively suppress (avoid or prevent) preferential corrosion of the joint.
[0114] Furthermore, as shown in FIG. 8, when the Cu concentrations of Example 1 and the Comparative Example are plotted with the initial Cu concentration of the core material on the horizontal axis and the Cu concentration of the joint on the vertical axis, it is found that a proportional relationship is established.
[0115] Furthermore, as shown in Figure 9, even if both sides of the brazing sheet are sacrificial anode material layers (Example 2), it can be seen that preferential corrosion of the joint can be effectively suppressed (avoided or prevented) as in the configuration in which a brazing material layer is formed on one side of the brazing sheet and a sacrificial anode layer is formed on the other side (Example 1).
[0116] The present invention is not limited to the above-described embodiment, and various modifications are possible within the scope of the claims. The technical scope of the present invention also includes embodiments obtained by appropriately combining the technical means disclosed in different embodiments or multiple modified examples. [Industrial Applicability]
[0117] The present invention can be suitably used not only in the field of brazing sheets for heat exchangers having a sacrificial anode material layer, but also in the field of heat exchangers using the brazing sheets. [Explanation of symbols]
[0118] 10: Brazing sheet 10a: Joint surface 10b: Non-bonded adjacent surfaces 11: Heartwood 12: Brazing material layer 13: Sacrificial anode layer 20: Brazing sheet joint structure 21: Joint 22: Fillet 30: Plate fin laminate 31: End plate 32: Plate fin 33:Header opening 34: Plate fin laminate 35: Plate fin 40: Parallel flow capacitor (PFC) 41: Header pipe 42:Flat tube 43: Corrugated fin
Claims
1. A brazing sheet used in an acute angle joint structure in a heat exchanger including an acute angle joint structure, the brazing sheet having joint surfaces that form a joint by being joined together and non-joint adjacent surfaces that are flat surfaces adjacent to the joint surfaces, the angle formed by each of the flat non-joint adjacent surfaces being an acute angle, and a fillet formed by sacrificial anode material flowing out from the joint surfaces and solidifying is formed in a portion between the non-joint adjacent surfaces and adjacent to the joint surfaces, An aluminum alloy core; a brazing material layer formed of an aluminum alloy brazing material containing silicon (Si) and covering one surface of the core material; A sacrificial anode material layer is coated on the other surface of the core material, the sacrificial anode material being made of an aluminum alloy containing zinc (Zn) in the range of 0.5 to 6.0 mass% and silicon (Si) in the range of 3.0 to 11 mass%, and forming the joining surface; Equipped with The brazing material and the sacrificial anode material do not contain copper (Cu) at a concentration exceeding unavoidable impurities; The core material contains copper (Cu) in the range of 0.3 to 1.2 mass %. Brazing sheet for joining structures of heat exchangers.
2. A brazing sheet used in an acute angle joint structure in a heat exchanger including an acute angle joint structure, the brazing sheet having joint surfaces that form a joint by being joined together and non-joint adjacent surfaces that are flat surfaces adjacent to the joint surfaces, the angle formed by each of the flat non-joint adjacent surfaces being an acute angle, and a fillet formed by sacrificial anode material flowing out from the joint surfaces and solidifying is formed in a portion between the non-joint adjacent surfaces and adjacent to the joint surfaces, An aluminum alloy core; A sacrificial anode material layer is coated on both surfaces of the core material, the sacrificial anode material being made of an aluminum alloy containing zinc (Zn) in the range of 0.5 to 6.0 mass% and silicon (Si) in the range of 3.0 to 11 mass%, at least one of which forms the joining surface; Equipped with The sacrificial anode material does not contain copper (Cu) in a concentration exceeding unavoidable impurities; The core material contains copper (Cu) in the range of 0.3 to 1.2 mass %. Brazing sheet for joining structures of heat exchangers.
3. The core material is an aluminum alloy of any one of 3000 series, 5000 series, and 6000 series to which copper has been added within the above range, The sacrificial anode material layer is a 4000 series aluminum alloy to which zinc has been added within the above range. The brazing sheet for a joining structure of a heat exchanger according to claim 1 or 2.
4. The brazing material layer is made of a 4000 series aluminum alloy. The brazing sheet for a joining structure of a heat exchanger according to claim 1.
5. The acute angle formed by each of the non-joint adjacent surfaces is within the range of 40° to 80°. The brazing sheet for a joining structure of a heat exchanger according to any one of claims 1 to 4.
6. A joint structure used for a member constituting a heat exchanger, in which brazing sheets each having an aluminum alloy core material and a sacrificial anode material layer formed of a sacrificial anode material on at least one surface of the core material are joined together, The brazing sheet has a joining surface and a non-joint adjacent surface which is a flat surface adjacent to the joining surface, each of the bonding surfaces being a layer of sacrificial anode material; The angle formed by each of the flat non-joint adjacent surfaces is an acute angle, and a fillet is formed of the sacrificial anode material that has flowed out from the joint surface and solidified at a portion between the non-joint adjacent surfaces and adjacent to the joint surface, The fillet contains copper (Cu) at a concentration exceeding that of the core material and the sacrificial anode material layer, and is 2.0% by mass or less. Brazing sheet joint structure.
7. The sacrificial anode material is an aluminum alloy containing zinc (Zn) in the range of 0.5 to 6.0 mass% and silicon (Si) in the range of 3.0 to 11 mass%, The core material before joining contains copper (Cu) in the range of 0.3 to 1.2 mass %, The sacrificial anode material before bonding does not contain copper. A brazing sheet joint structure according to claim 6.
8. When the sacrificial anode material layer is coated on only one surface of the core material, the other surface is coated with a brazing material layer made of a brazing material. A brazing sheet joint structure according to claim 7.
9. The brazing material is an aluminum alloy containing silicon (Si), and the brazing material before joining does not contain copper. A brazing sheet joint structure according to claim 8.
10. The fillet contains zinc (Zn), and the concentration of copper (Cu) in the fillet is higher than the concentration of zinc. A joint structure of the brazing sheet according to claim 7 or 9.
11. The acute angle formed by each of the non-joint adjacent surfaces is within the range of 40° to 80°. A brazing sheet joint structure according to any one of claims 6 to 10.
12. A brazing sheet joint structure according to any one of claims 6 to 11, heat exchanger.
13. A plate-fin stacked heat exchanger or a parallel flow condenser (PFC), 13. The heat exchanger of claim 12.
Citation Information
Patent Citations
Multilayer type aluminum heat exchanger with good corrosion resistance
JP1996303988A
Aluminum alloy cladding material
JP2009155679A
Aluminum alloy brazing sheet having excellent strength and corrosion resistance
JP2010163674A
High corrosion resistant aluminum alloy brazing sheet, and flow path forming component for automotive heat exchanger using the same
JP2013155404A